The Investigation of LRP5-Loaded Composite with Sustained Release Behavior and Its Application in Bone Repair. (5th February 2019) - Xi, Yanhai; Jiang, Tingwang; Yu, Jiangming; Xue, Mintao; Xu, Ning; Wen, Jiankun; Wang, Weiheng; He, Hailong; Ye, Xiaojian
Abstract : Low-density lipoprotein receptor-related protein 5 (LRP5) plays a vital role in bone formation and regeneration. In this study, we developed an injectable and sustained-release composite loading LRP5 which could gelatinize in situ. The sustained release of the composite and its efficacy in bone regeneration were evaluated. Sodium alginate, collagen, hydroxyapatite, and LRP5 formed the composite LRP5-Alg/Col/HA. It was found that the initial setting time and final setting time of LRP5-Alg/Col/HA containing 4% alginate were suitable for surgical operation. When the composite was loaded with 40  μ g/mL LRP5, LRP5-Alg/Col/HA did not exhibit a burst-release behavior and could sustainably release LRP5 up to 21 days. Up to 18 days, LRP5 released from LRP5-Alg/Col/HA still present the binding activity with DKK1 (Wnt signaling pathway antagonist) and could increase the downstream β -catenin mRNA in bone marrow mesenchymal stem cells. Moreover, LRP5-Alg/Col/HA was found to significantly increase bone mineral density in the defect area after 6 weeks' implantation of LRP5-Alg/Col/HA into the rats' calvarial defect area. H&E staining detection demonstrated that LRP5-Alg/Col/HA could mediate the formation of a new bone tissue. Therefore, we concluded that Alg/Col/HA was a suitable sustained-release carrier for LRP5 and LRP5-Alg/Col/HA had a significant effect on repairing bone defects and could be a good bone regeneration material.